EVALUASI PROGRAM PEMBELAJARAN MELALUI DARING SELAMA WORK FROM HOME COVID-19 - Alfa Mitri Suhara (STKIP Siliwangi, 2021)
The emergence of Covid-19 in various countries including Indonesia has become a problem that has taken a lot of public attention and has an impact in every area of people's lives, including education. Since it was announced that Covid-19 is a pandemic that needs to be addressed immediately and appropriately, the education sector from PAUD to tertiary institutions has taken a big step, namely carrying out bold learning. This decision was taken to maintain the quality of learning and the output of students in order to maintain good competence. To ensure that there are many factors that become successes or obstacles to the implementation of learning, then evaluate it appropriately so that the objectives of the learning implementation are achieved. Based on this description, this study aims to determine the quality of the learning program through work from home Covid-19 in the IKIP Siliwangi environment. This research method is descriptive qualitative. The results of the study are known from the distribution of questionnaires and observation sheets used in collecting data on the learning program through courage during the Covid-19 pandemic, as seen from the answers to the questionnaire and the acquisition of observation sheets with a percentage of 70%. Thus, it can be said that the results of the evaluation of the future learning program for the Covid-19 pandemic in the IKIP Siliwangi environment with a sample of thirty-five students went well and effectively.